Mental Well-Being of Older People in Finland during the First Year in Senior Housing and Its Association with Physical Performance - Sinikka Lotvonen; Helvi Kyngäs; Pentti Koistinen; Risto Bloigu; Satu Elo (International Journal of Environmental Research and Public Health, 2018)
Growing numbers of older people relocate to senior housing, when their physical or mental performance declines. The relocation is known to be one of the most stressful events in the life of older people and affect their mental and physical well-being. More information about the relationships between mental and physical parameters is required. We examined self-reported mental well-being of 81 older people (aged 59–93, living in northern Finland), and changes in it 3 and 12 months after relocation to senior housing. The first measurement was 3 months and the second measurement 12 months after relocation. Most participants were female (70%). Their physical performance was also measured, and associations between these two were analyzed. After 12 months, mental capability was very good or quite good in 38% of participants, however 22% of participants felt depressive symptoms daily or weekly. Moreover, 39% of participants reported daily or weekly loneliness. After 12 months participants reported a significant increase in forgetting appointments, losing items and difficulties in learn new things. They felt that opportunities to make decisions concerning their own life significantly decreased. Furthermore, their instrumental activities of daily living (IADL), dominant hand’s grip strength and walking speed decreased significantly. Opportunities to make decisions concerning their life, feeling safe, loneliness, sleeping problems, negative thoughts as well as fear of falling or having an accident outdoors were associated with these physical parameters. In addition to assessing physical performance and regular exercise, the various components of mental well-being and their interactions with physical performance should be considered during adjustment to senior housing.